Legal Aspects of the Establishment and Development of the University of Maribor - Ivanjko, Šime; Knez, Rajko; Legat, Dunja; Tancer Verboten, Mojca (50 let Univerze v Mariboru: Pol stoletja znanja in raziskovanja, 2026)
This chapter discusses the development milestones of the University of Maribor, from the legal aspects of its establishment. For 50 years, Maribor has been home to an internationally recognized University with numerous educational programmes and scientific research areas implemented by 17 faculties and two members providing support in the field of librarianship and student housing. The development of the University in the city of Maribor reflects its historical growth, response to social and economic needs, and the formation of its identity. Since its establishment in 1975, the process of status organization and operation of the University of Maribor and its faculties has been carried out in accordance with the provisions of higher education legislation. Based on Article 40 of the »Constitution of the Socialist Republic of Slovenia« (1974) and Article 9 of the »Higher Education Act« (1975), amendments and supplements to the Self-Government Agreement on the merger of six higher education working organizations into the University of Maribor were signed on June 11, 1976. These organizations had been transformed over the past 50 years, new faculties were established, and the University of Maribor, regardless of its name, expanded to other parts of Slovenia.